2004
DOI: 10.1111/j.1529-8817.2004.03076.x
|View full text |Cite
|
Sign up to set email alerts
|

ENVIRONMENTAL EFFECTS ON EXOPOLYMER PRODUCTION BY MARINE BENTHIC DIATOMS: DYNAMICS, CHANGES IN COMPOSITION, AND PATHWAYS OF PRODUCTION1

Abstract: Marine benthic diatoms excrete large quantities of extracellular polymeric substances (EPS), both as a function of their motility system and as a response to environmental conditions. Diatom EPS consists predominantly of carbohydrate-rich polymers and is important in the ecology of cells living on marine sediments. Production rates, production pathways, and monosaccharide composition of water-soluble (colloidal) carbohydrates, EPS, and intracellular storage carbohydrate (glucans) were investigated in the epipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
222
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(243 citation statements)
references
References 58 publications
12
222
1
5
Order By: Relevance
“…The change in colony shape and appearance at the end of Phaeocystis blooms (e.g., Verity et al 1988;Rousseau et al 1994) is therefore not reflected in the aldose composition of the mucopolysaccharides. This is different from the situation reported in diatoms, where upon nutrient limitation, the benthic diatom Cylindrotheca closterium excretes a separate extracellular polysaccharide with a different monosaccharide composition compared to optimal growth conditions (De Brouwer et al 2002;Underwood et al 2004). Phaeocystis acts as a secretory cell; mucopolysaccharides are excreted in a way similar to animal cells and vascular plants in which the regulated export of cellular products takes place via exocytosis.…”
Section: Mucopolysaccharidescontrasting
confidence: 45%
“…The change in colony shape and appearance at the end of Phaeocystis blooms (e.g., Verity et al 1988;Rousseau et al 1994) is therefore not reflected in the aldose composition of the mucopolysaccharides. This is different from the situation reported in diatoms, where upon nutrient limitation, the benthic diatom Cylindrotheca closterium excretes a separate extracellular polysaccharide with a different monosaccharide composition compared to optimal growth conditions (De Brouwer et al 2002;Underwood et al 2004). Phaeocystis acts as a secretory cell; mucopolysaccharides are excreted in a way similar to animal cells and vascular plants in which the regulated export of cellular products takes place via exocytosis.…”
Section: Mucopolysaccharidescontrasting
confidence: 45%
“…However, in many cases, bacteria acting on and influencing the fresh phytoplankton DOM pool creates uncertainties in the magnitude of C and N fluxes to that pool. In the case of the short-term 14 C tracer studies, Underwood et al (2004) found that there was an ,3-h time lag between addition of 14 C label to diatom cultures and the subsequent production of labeled extracellular polysaccharides, a potentially large component of phytoplankton-derived DOM. Thus, short (less than a few hours) 14 C studies may completely miss C dynamics associated with the extracellular polysaccharide pool, a point noted in the earlier studies of Mague et al (1980) and Smith (1982).…”
Section: Discussionmentioning
confidence: 99%
“…TEP plays an important role in the biogeochemistry of the biological carbon pump (Passow & Carlson, 2012) and consequently there is a need to better define its composition to determine its origin and biogeochemical significance. Much of the recent detailed work on the composition of EPS produced by diatoms has been conducted with laboratory-grown cultures of benthic epipelic diatoms (Underwood et al, 2004;Bellinger et al, 2005;Abdullahi et al, 2006). There is no reason why the techniques used in this research could not be applied to ecologically relevant taxa of phytoplankton.…”
Section: Chemical Characterization Of Dom Released By Phytoplanktonmentioning
confidence: 99%